Explorative research on health literacy and self-care management of type 2 diabetes mellitus in Malaysia - Ahmad Azhari, Azrina Ely (2024)
Type 2 diabetes is a chronic metabolic disorder which affects 3.9 million people in Malaysia in 2019. The prevalence of diabetes in the country is expected to rise as a result of unhealthy diet and sedentary lifestyle. As a complex disease, effective pharmacological management is key, in addition to the adoption of healthy self-care behaviours by patients. However, many patients with type 2 diabetes struggled to maintain their glycaemic control and adopt self-care measures due to various reasons which include low health literacy. Low health literacy among diabetes patients may result in poor self-care management and diabetes outcome. Pharmacists play a major role in patient education especially on medication adherence and diabetes self-care as they are easily accessible to the public. The accessibility of pharmacy services to the public may aid diabetes patients with health literacy challenges getting advice and support they need in empowering self-care.